Climate Disruption: Are We Beyond the Worst Case Scenario?. Issue 1 (3rd September 2012) - Jennings, Michael
<x xml:space="preserve">Abstract</x> Abstract The inability of world governments to agree on and implement effective mitigation response policy for anthropogenic climate change has resulted in the continuation of an exponential growth in greenhouse gas emissions (GHGs) that averages 3.1 per cent per year since 1870. With the exception of 2009, world GHG emission levels surpassed the Intergovernmental Panel on Climate Change (IPCC) (2000) worst case scenario every year since 2004. Because of increasing temperatures due to GHG emissions a suite of amplifying feedback mechanisms, such as massive methane leaks from the sub‐sea Arctic Ocean, have engaged and are probably unstoppable. These processes, acting in concert with the biological and physical inertia of the Earth system in responding to atmospheric loading of GHGs, along with economic, political and social barriers to emission reduction, currently place Earth's climate trajectory well within the IPCC's A1FI future climate change scenario. There is a rapidly diminishing chance of altering this trajectory as time goes on. There is also now a very real risk of sudden climate change. The pace of this quickly advancing situation, along with our scientific understanding of it, has substantially outstripped policy discussion. This article examines current primary science literature and data on today's climate condition in a policy relevant context. Policy Implications An all out shift to a broad range of adaptive response policies is urgently needed. Climate change will force reevaluations of present day governance agreements on trade, finance, food supply, security, development, environment, and similar sectors. Easy to understand scientific data driven visualizations and culturally appropriate interpretations of probable future conditions are needed to facilitate realistic adaptive policy responses from all levels of governance. Multilateral policies for an international crop seed cooperative could significantly lessen the impacts of crop failures and low yields, reducing the risk of famine and economic effects of unstable food prices. There is a need to store a large enough volume of crop seed varieties to allow for quick switching of varieties one year to the next based on dynamic forecasts of seasonal climates. Harmonization of international, national, subnational, and local policies for the orderly resettlement of coastal populations should begin now. This will become a chronic condition involving very large numbers of people. Improved and coordinated policies are needed for refugee services and related issues of migration and integration as well as planning for land use change and infrastructure development.